Under-Frequency Load Shedding scheme for islanded distribution network connected with mini hydro - Karimi, M.; Mohamad, H.; Mokhlis, Hazlie; Bakar, A.H.A. (International Journal of Electrical Power & Energy Systems, 2012)
Under-Frequency Load Shedding (UFLS) is a common technique to maintain power system stability by removing the overload in some part of the system. The existing UFLS schemes operate successfully in the interconnected grid system. A particular approach of UFLS scheme is required for an islanded system which is known to be not as strong as the grid. This paper presents a new approach of UFLS scheme for the implementation in an islanded distribution system. The scheme is based on a combination of adaptive and intelligent techniques. The disturbance magnitude for response based and event based is treated differently: (1) event based is based on the power imbalance and (2) response based is based on the swing equation which relies on the frequency and rate of change of frequency measurement. Dynamic simulation on an intentional islanding operation is performed on an existing Malaysian network interconnected with a mini hydro generation. The objective is to investigate the effectiveness of the proposed scheme. The simulation results demonstrate that the proposed scheme is capable of improving the frequency response of the islanded system. A significant finding is that the scheme can successfully reduce the effect of power deficiency following the grid connected to islanding operation transition.